Cell‐free ribosome display and selection of antibodies on arrayed antigens. Issue 8 (4th April 2016) - Cong, Cong; Yu, Xin; He, Yongzhi; Dai, Yujian; Zhang, Yongxia; Wang, Mingrong; He, Mingyue
Abstract : In vitro display technology is a powerful tool for discovery and optimisation of novel antibodies. With increasing demands on various binding molecules in proteomics studies, techniques for a large‐scale generation of antibodies or antibody fragments are needed. Here, we describe a novel method for parallel generation of different antibody fragments (scFv) by integrating cell‐free ribosome display with array technology. We have demonstrated the procedure by successfully isolating scFv antibodies specific to 16 different cancer biomarkers via a single process. Our results provide proof of principle for multiple production of various scFv antibodies simultaneously.